Identification and quantitative expression of valuation uncertainty at the property market - Kalynichenko, Uliia (Technology audit and production reserves, 2016)
The sources of objective, subjective and model valuation uncertainty at the property market are investigated. It is determined that the sources of objective uncertainty are the stochastic nature of the property market, incompleteness and inconsistency of market information. The sources of subjective uncertainty are a low level of analyst qualification and model uncertainty – inadequate valuation model or incorrect of chosen valuation method. It is proved that an approach to valuation of the quality of the results, which is based on the error concept, is deterministic, it is associated with the presence of errors (systematic and random) of measuring instruments and is the frequency interpretation of probability. In approach, which is based on the uncertainty concept, the uncertainty of results is associated exclusively with the measurement process, and not with the measuring instruments. It is a subjective interpretation of probability, which characterizes the degree of confidence. It is proved that the use of more appropriate pricing models makes it possible to understand the complex risks and their impact on management decisions at the property market, but not eliminates an uncertainty.